Electrical properties of textured (KNa)0.44Li0.06Nb0.84Sb0.06Ta0.1O3 thick films - Fu, Fang (2013)
Lead-free (KNa)0.44Li0.06Nb0.84Sb0.06Ta0.1O3 textured thick films with 25 μm thickness were fabricated by the reactive templated grain growth method. The influence of LiSbO3 substitution on the degree of grain orientation was investigated. The addition of LiSbO3 improved the dielectric properties of the K0.5Na0.5NbO3 potassium sodium niobate (KNN) textured thick films. Leakage current behavior of the thick film was also reduced due to the LiSbO3 doping, which is explicable based on the space-charge-limited current mechanism. It was also found that the problem of interface effect was alleviated due to the presence of LiSbO3. Piezoelectric properties of thick film were improved dramatically owing to the co-effect of texturing and LiSbO3 doping, with d 33 * being sharply increased from 38 pm/V to 173 pm/V.